2014
DOI: 10.1002/humu.22563
|View full text |Cite
|
Sign up to set email alerts
|

TCIRG1-Associated Congenital Neutropenia

Abstract: Severe congenital neutropenia (SCN) is a rare hematopoietic disorder, with estimated incidence of 1 in 200,000 individuals of European descent, many cases of which are inherited in an autosomal dominant pattern. Despite the fact that several causal genes have been identified, the genetic basis for >30% of cases remains unknown. We report a five generation family segregating a novel single nucleotide variant (SNV) in TCIRG1. There is perfect co-segregation of the SNV with congenital neutropenia in this family; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…The results of this study provide supportive evidence for a role of TCIRG1 variation in determining ANC. Having previously shown that a single TCIRG1 variant co‐segregated and was associated with ANC [Makaryan et al., ], we now additionally demonstrate an association between rare, coding variants at conserved sites in TCIRG1 and ANC. Notably the more rare of these variants were associated with lower ANC than the ones seen in more than one individual, suggesting a spectrum of effect sizes may be associated with different variants.…”
Section: Discussionsupporting
confidence: 74%
“…The results of this study provide supportive evidence for a role of TCIRG1 variation in determining ANC. Having previously shown that a single TCIRG1 variant co‐segregated and was associated with ANC [Makaryan et al., ], we now additionally demonstrate an association between rare, coding variants at conserved sites in TCIRG1 and ANC. Notably the more rare of these variants were associated with lower ANC than the ones seen in more than one individual, suggesting a spectrum of effect sizes may be associated with different variants.…”
Section: Discussionsupporting
confidence: 74%
“…Recombinant human granulocyte-colony stimulating factor (G-CSF) (for example filgrastim and lenograstim became available for clinical research in 1987 10 and was approved by the FDA for the treatment of congenital neutropenia in 1993 (Ref 14 ). First description of the: GFI1 gene mutation 150 the CXCR4 151 TCIRG1 152 . First description of the acquired CSF3R mutations in severe congenital neutropenia patients 153 …”
Section: Figurementioning
confidence: 99%
“…3 In many instances, knowing the pedigree that is consistent with the generated genetic data is crucial to solving the disease. [4][5][6][7] Additionally, the collection of samples from a limited geographical region for a genetic analysis might introduce biases toward unintentionally obtaining samples of unknown relatedness for which a previously unknown pedigree could be reconstructed and used. As a result, large case-control consortia can harbor cryptic relatedness, 8 which can bias the analysis unless the cryptic relatedness is removed or investigators use a method that models a kinship matrix.…”
Section: Introductionmentioning
confidence: 99%